Semantic field of health in the Hispanic toponymic discourse - Martynenko, Irina (Onomástica desde América Latina, 2025)
Health and medical toponyms are not the most numerous groups in the toponomastics of the world, however, present an important part of the history of a city where they function. The article analyzes the extensive lexical-semantic field of health in Hispanic toponymy of the world in the aspect of its constituting units’ distribution. By means of the GeoNames electronic database, material for the study was selected using the continuous sampling method. The functioning of such units is analyzed from the pragmatic point of view, numerous examples are given. The boundaries of the core and peripheral region of the field are determined. It is established, in particular, that in Paraguay and Uruguay toponyms are associated with the names of outstanding doctors and scientists. And the generalizing concept of Medicina – the Spanish for “medicine” (mainly) – is a component that appears mostly in the urban toponymy. There are also Latin American cities named after diseases. The author comes to the conclusion that the meliorative connotation within this semantic field prevails over the pejorative one. And the linguistic parameters obtained can be viewed as markers of the national identity in toponymy of the indicated regions which are isosemic to the spread of the Spanish language on these terrritories. Parallels are drawn between the semantic field of health, developed by Russian toponymists in the field of regional onomastics, and that in the field of Hispanic toponymy. It is demonstrated that the most abundant Hispanic toponymic unit within the theme of health is Salud which is “health” for Spanish and the core or concept of the considered semantic field. Some place names can be attributed the “health” semantic field only with due caution as they belong to another semantic category. The article contributes to the development of the theory of the semantic field, national identity, toponomastics and linguodidactics.